(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The article deals with problem solving of mathematical physics using the method of separation of variables optimizing heating element – optimizing water tube parameters (tube material, radius, insulation thickness, choosing appropriate surrounding environment). For ensuring piglets comfort, concrete floor panels heated by electric current or hot water are used. If an electro-heated cable in the panels body is placed, than amount of heat conducted from the cable is the same along all the length of the cable. If hot water circulating through tube is used, than amount of heat energy taken off the heater decreases along its length. The aim of the research is to create the mathematical model of a water tube, were water temperature is gradually decreasing. This model is needed to make precise calculations of the heating panel for piglets, to ensure equal temperature distribution over the upper surface of the panel, taking into account mathematically calculated temperature decrease of the heat source.